-28=2-3(4-3n)

Simple and best practice solution for -28=2-3(4-3n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -28=2-3(4-3n) equation:


Simplifying
-28 = 2 + -3(4 + -3n)
-28 = 2 + (4 * -3 + -3n * -3)
-28 = 2 + (-12 + 9n)

Combine like terms: 2 + -12 = -10
-28 = -10 + 9n

Solving
-28 = -10 + 9n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-9n' to each side of the equation.
-28 + -9n = -10 + 9n + -9n

Combine like terms: 9n + -9n = 0
-28 + -9n = -10 + 0
-28 + -9n = -10

Add '28' to each side of the equation.
-28 + 28 + -9n = -10 + 28

Combine like terms: -28 + 28 = 0
0 + -9n = -10 + 28
-9n = -10 + 28

Combine like terms: -10 + 28 = 18
-9n = 18

Divide each side by '-9'.
n = -2

Simplifying
n = -2

See similar equations:

| 5X^2+3X+8= | | -6v=-14 | | 8a^3=p^2 | | 11a=30+8a | | 6x-6-4x=6x-5 | | =-14-6v | | 9b=81 | | -x+4x=18 | | 2(2x-138)=x+24 | | 2x+3(.25x)=55 | | 4x+-8=18 | | 5f=-50 | | 4-6+5x= | | 4=-9 | | -7-(-8)=x | | 10.3x-32=-7x+28 | | (2x-(-4))(3x+(-2))=3-(5-3x)(2x+3) | | =h(a+b) | | -7-6=x | | 10x-11x+3=0 | | -9-3=x | | n-9=-42 | | -5(6m-3)=38-7m | | -10+4x=-42 | | 0.88=log(x) | | 2(9x+631)=2x+270 | | .88=log(x) | | 1-5b-4b=10 | | 11z=-100 | | 3n-9+3=24 | | 3(14-4y)-5y=-9 | | 6y+5=10y-1 |

Equations solver categories